Provision Of Non-Civil Servant Workforce in Participating in The Selection of Government Employees with Work Agreements - Urohman, Taufiq (International Conference On Economics Business Management And Accounting (ICOEMA), 2024)
Working as a State Civil Apparatus (ASN) is still quite an attractive job for the community. Since 2021, ASN procurement has focused on procuring Government Employees with Work Agreements (PPPK). Becoming a PPPK is not easy because you have to go through a strict selection and its implementation is simultaneously held by the State Civil Service Agency. One effort to maximize the occupancy of PPPK formations is by providing training to non-ASN personnel. The aim of this activity is to increase the competency of non-ASN personnel who will take part in the PPPK procurement selection. The method used is by providing material through presentation of how to answer questions about PPPK procurement in order to get a high score and simulating answering practice questions according to the field of position to be applied for. Participants are given time to answer practice questions contained in the application provided by the Regional Civil Service Agency of East Java Province. The debriefing activity can increase in the competency of non-ASN staff, as well as the readiness of prospective test participants to take part in the PPPK procurement selection with the hope of being able to fill the existing PPPK formation.